2009
DOI: 10.1142/s0218001409007284
|View full text |Cite
|
Sign up to set email alerts
|

Robust Adapted Principal Component Analysis for Face Recognition

Abstract: Recognizing faces with uncontrolled pose, illumination, and expression is a challenging task due to the fact that features insensitive to one variation may be highly sensitive to the other variations. Existing techniques dealing with just one of these variations are very often unable to cope with the other variations. The problem is even more difficult in applications where only one gallery image per person is available. In this paper, we describe a recognition method, Adapted Principal Component Analysis (APC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The problem is even more difficult in applications where only one gallery image per person is available. Chen, Lovell and Shan [8] describe a recognition method, Adapted Principal Component Analysis (APCA), which can simultaneously deal with large variations in both illumination and facial expressions using only a single gallery image per person. Experimental results show that APCA performs much better than other recognition methods including PCA and LDA.…”
Section: Subspace Based Statistical Methodsmentioning
confidence: 99%
“…The problem is even more difficult in applications where only one gallery image per person is available. Chen, Lovell and Shan [8] describe a recognition method, Adapted Principal Component Analysis (APCA), which can simultaneously deal with large variations in both illumination and facial expressions using only a single gallery image per person. Experimental results show that APCA performs much better than other recognition methods including PCA and LDA.…”
Section: Subspace Based Statistical Methodsmentioning
confidence: 99%
“…Unsupervised DR is an important and necessary branch of DR techniques as collections of plentiful unlabeled samples are easy but achievements of class information are relatively expensive. 31 Principal Component Analysis (PCA) 8,15 is one of the most popular unsupervised DR algorithms. It seeks a set of orthogonal projection vectors that best represents the data in the least-squares sense by maximizing the scatter of data.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the locality-based LPP can usually preserve the manifold structure in the embedding space to a certain extent, and thus is relatively e®ective on some classi¯cation tasks (e.g. face recognition 8,13 ). As a result, the \locality" idea is constantly generalized, and thus many locality-based dimensionality reduction (DR) algorithms have successively been proposed, typically including unsupervised Unsupervised Discriminant Projection (UDP) a29 and OLPP, 6 semi-supervised discriminant analysis 5,26 and supervised MFA, 24 LDE, 7 ANMM, 23 GSSGE, 30 etc.…”
Section: Introductionmentioning
confidence: 99%